Influence of Solvent upon Reactive Capacity of Ozone in Respect of 1, 3-Dimethyl-Substituted Uracils. (4th March 2023) - Maksyutova, Aigul A.; Zimin, Yuriy S.; Mustafin, Akhat G.
ABSTRACT: Reactive capacity of ozone in respect of three representatives of the nitrogenous bases (1, 3-dimethylthymine, 1, 3, 6-trimethyluracil, and 5-hydroxy-1, 3, 6-trimethyluracil) in two solvents having different polarities (Н2 О and CCl4 ) was investigated with the help of the ultraviolet spectroscopy method. At the first stage of investigations, coefficients of extinction of 1, 3-DMU in the selected solvents were determined. At the next stage, kinetics of absorption of ozone by solutions of 1, 3-dimethyl-substituted uracils at room temperature (295°K) was studied with the help of the bubbling equipment. It was established that parent compounds (О3 and 1, 3-DMU) react in the equimolar relationships, that is, 1 g-mol of the consumed uracil corresponds to 1 g-mol of the absorbed ozone. On the basis of the data on the stoichiometry and kinetics of consumption of the parent compounds, obvious and definitive conclusion was made: the reactions under investigation comply with the kinetic law of the second order (of the first order – in respect of О3 and of the first order – in respect of 1, 3-DMU). In the course of further investigations, temperature (from 285°K up to 309°K) dependences of constants of velocities of the second order were investigated, as well as parameters of the Arrhenius equation in respect of reactions of ozone were determined. It was established that the reaction rate constants of reactions between ozone and 1, 3-DMU within the medium of the nonpolar organic solvent (CCl4) exceed the reaction rate constants within the medium of the polar solvent (Н2 О).